2004
DOI: 10.1111/j.1492-7535.2004.80406.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin‐I and its prognostic significance in a dialysis population

Abstract: cT-I has a high specificity for the diagnosis of myocardial infarction in dialysis patients. Despite the relatively low number of positive test results, cT-I was found to be significantly correlated with the outcome all-cause mortality at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
3
0
6
Order By: Relevance
“…The results of a study carried out by Hussein et al on 93 asymptomatic HD patients showed that cTnI significantly correlated with the outcome of all-cause mortality after one year (17).…”
Section: Discussionmentioning
confidence: 96%
“…The results of a study carried out by Hussein et al on 93 asymptomatic HD patients showed that cTnI significantly correlated with the outcome of all-cause mortality after one year (17).…”
Section: Discussionmentioning
confidence: 96%
“…in their study on 93 asymptomatic HD patients showed that cTnI has a high specificity for the diagnosis of myocardial infarction in dialysis patients and it was found to be significantly correlated with the outcome of all-cause mortality at 1 year. [ 20 ] Resic et al . reported that periodical hemodynamics or underlying cardiac disease with specific alterations of cardiac musculature in uremia would be some possible reasons for cTnI elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated serum cTnT levels are frequently observed in asymptomatic chronic dialysis patients [12] and have been shown to be associated with increased morbidity and mortality [13,14,15,16,17], although other reports [18, 19] found cTnT to be of no predictive value. cTnI, which is less frequently elevated, has also been associated with increased morbidity and mortality [20, 21]. However, cTnT has been found to be less specific than cTnI for the diagnosis of acute cardiac event in ESRD patients [22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%